AUTOMATED CROSS-PLATFORM DATABASE MIGRATION AND HIGH AVAILABILITY IMPLEMENTATION - MARUTHI LAKSHMI GANESH NERELLA, VEERAVENKATA (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
The increasing reliance on data-driven decision-making in businesses and organizations has made database migration a critical aspect of modern IT infrastructures. Cross-platform database migration, while vital for evolving technological landscapes, comes with a host of challenges. This paper presents an in-depth study on automated cross-platform database migration and high availability implementation. The research focuses on the automation of the migration process, which allows for the seamless transition of databases between different platforms, such as from on-premises systems to cloud platforms. It explores the implementation of high availability (HA) mechanisms to ensure the uninterrupted operation of databases during migration, reducing downtime and minimizing the risks of data loss. The study investigates the various tools and technologies employed in the automated migration process, including real-time replication, disaster recovery, and failover systems. Through comprehensive case studies, we demonstrate how automated tools improve the efficiency and reliability of migration while maintaining system availability. A significant portion of the paper discusses the underlying technical considerations of setting up automated migration environments, such as ensuring data integrity, schema compatibility, and minimal service disruption. This research aims to provide organizations with a framework for understanding the key challenges and best practices associated with cross-platform database migration and high availability. It also offers recommendations for leveraging automation to enhance operational efficiency. The results underscore the importance of effective migration planning and choosing the right set of tools to ensure success.